Tumor stem cells of malignant gliomas - Lisyany, A. N.; Lisyany, N. I. (Ukrainian Neurosurgical Journal, 2010)
Data of last researches, devoted to tumor stem sells, that are identified in malignant gliomas, are given. Tumor stem cells are similar to ordinary neural stem cells of the brain. They express CD133+ molecule marker, are able to migrate and infiltrate intact brain tissue. They cause relapses and recurrent growth of malignant tumors. Tumor stem cells are resistant to chemical and radiotherapy and lead to growth tumor at experimental animals with ummunodeficit. Tumor stem cells — are a new subject for investigation and development of new treatment strategies for brain gliomas.